2014
DOI: 10.1111/cge.12354
|View full text |Cite
|
Sign up to set email alerts
|

The communication of secondary variants: interviews with parents whose children have undergone array‐CGH testing

Abstract: Children with unexplained developmental disabilities or congenital anomalies are increasingly being referred for genetic diagnostic testing using array-comparative genomic hybridisation (array-CGH) and next-generation sequencing (NGS) technologies. Their parents will have to deal with the secondary variants that will inevitably arise. We conducted 16 prospective semi-structured interviews with native Dutch-speaking parents whose children had undergone clinical array-CGH testing. The interviews explored the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Across different types of possible results, participants expressed interest in learning about health implications, risk and prevalence statistics, causes of the variant, and causes of diseases, both for themselves and for family members. The finding of the importance of health implications is consistent with prior literature; learning health information was a primary motivation to pursue genetic testing and genome sequencing in previous studies (Christenhusz et al 2014; Facio et al 2011; Hitch et al 2014; Leventhal et al 2013; O’Neill et al 2013; Wright et al 2014). For instance, focus group participants from a cohort undergoing clinical sequencing expected their results to provide information about their current or future health (Wright et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Across different types of possible results, participants expressed interest in learning about health implications, risk and prevalence statistics, causes of the variant, and causes of diseases, both for themselves and for family members. The finding of the importance of health implications is consistent with prior literature; learning health information was a primary motivation to pursue genetic testing and genome sequencing in previous studies (Christenhusz et al 2014; Facio et al 2011; Hitch et al 2014; Leventhal et al 2013; O’Neill et al 2013; Wright et al 2014). For instance, focus group participants from a cohort undergoing clinical sequencing expected their results to provide information about their current or future health (Wright et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Studies that have sought patient or parental views about disclosing IFs from whole-genome tests show that most respondents would want to be told about any result generated, because the perceived advantages (be they based on medical benefit or personal utility) outweigh the disadvantages of knowing 17 44 51 52. Findings from these studies could be poor predictors of actual decisions, since participants had not received IFs, and their views were gathered in response to hypothetical situations.…”
Section: Issues To Considermentioning
confidence: 99%
“…Indeed, when given a hypothetical case involving uncertain findings and IFs identified in a child, some clinicians did not find it important to discuss with parents the potential for such discoveries to be made 53. Clinicians have a duty to consider the welfare of their patients: if patients decide they do not want any information about IFs, clinicians might be faced with a dilemma about whether or not to disregard the patient's wishes to not know and disclose an IF that has a proven clinical intervention, particularly one that could have medical urgency 7 17 54 55. Yu et al 31 found that in clinical practice 68% (239/349) of clinicians offered to return IFs for Mendelian conditions, 47% (164/349) for adverse drug responses and 45% (157/349) for autosomal recessive carrier status (157/349).…”
Section: Issues To Considermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study of three focus groups with individuals who had prior preconception genetic testing experience demonstrated different perceptions of the advantages or disadvantages of screening within each group, suggesting tailored approaches to education, consent, and counseling may be warranted (Schneider et al, 2016). Another focus group on genetic testing involving children highlighted concerns about the return of secondary findings only because of the discussion that occurred in a group context (Christenhusz, Devriendt, Peeters, Van Esch, & Dierickx, 2014). Policy issues related to the disclosure of secondary findings resulting from genomic sequencing involve complex scientific, regulatory, and ethical considerations.…”
Section: Introductionmentioning
confidence: 99%